Identification of Grb2 protein as a potential mediator of macrophage activation in acute pancreatitis based on bioinformatics and experimental verification - Shen, Qinhao; Wang, Shuai; Wu, Keyan; Wang, Liuhui; Gong, Weijuan; Lu, Guotao; Chen, Weiwei; Yuan, Chenchen; Tu, Bo; Li, Wei; Wang, Yaodong; Yang, Weixuan (Frontiers in Immunology, 2025)
IntroductionMacrophage activation is closely associated with Acute pancreatitis (AP). We screened and found that Growth factor receptor bound protein 2 (Grb2) is highly expressed in macrophages during AP. However, the relationship between Grb2 and AP is still poorly understood. In this study, we explored the role of Grb2 in AP.MethodsWe screened for gene affecting macrophage activation in AP by combining transcriptomics with Single-cell RNA-sequence analysis. Next, the expression of Grb2 in M1/M2 macrophage activation was detected by Single-cell RNA-sequence analysis and western blot. Furthermore, the effect of Grb2 on M1/M2 macrophage activation was detected by flow cytometry. The severity of AP was assessed by histological analysis, serum amylase, serum lipase and serum inflammatory factors in vivo. NOD-like receptor thermal protein domain associated protein 3 (Nlrp3) and Nuclear factor kappa-B (NF-kB) signaling pathways were also evaluated.ResultsGrb2 is mainly expressed in macrophages of pancreas in AP and up-regulated in M1 macrophage activation. Inhibiting Grb2 could alleviate AP by preventing M1 macrophage activation through down-regulating Nlrp3 and NF-κB.DiscussionInhibition of Grb2 can effectively prevent M1 macrophage activation and alleviate AP. Grb2 may potentially be an effective target of macrophage activation for the treatment of AP.